Design, Baseline Results of Irbid Longitudinal, School-based Smoking Study - Mzayek, Fawaz (Am J Health Behav, 2011)
OBJECTIVE: To compare patterns of water pipe and cigarette smoking in an eastern Mediterranean country. METHODS: In 2008, 1781 out of 1877 seventh graders enrolled in 19 randomly selected schools in Irbid, Jordan, were surveyed. RESULTS: Experimentation with and current water pipe smoking were more prevalent than cigarette smoking (boys: 38.7% vs 26.8%; 20.2% vs 9.0%, girls: 21.2% vs 9.5%; and 7.5% vs 2.3%, P<0.05 for all). Parent- and peer-smoking correlated more strongly with water pipe than with cigarette smoking. CONCLUSION: Water-pipe smoking is more prevalent than cigarette smoking at this early age.